Space odyssey : a voyage to the planets - Haines, Tim, author 565573; Riley, Christopher, author 565574 (London : BBC Books, 2004)
It will be the greatest adventure that humans have ever embarked on. Six years in space, away from Earth, voyaging further and faster than anyone before them. Demanding the courage to face incredible dangers, it is a quest that will define new frontiers for our species. This is the story of Project Pegasus, the first manned voyage to the planets. Witness, through the eyes of the five astronaut-explorers, the extraordinary sights of our solar system: the superheated lava fields of volcanic Venus, gigantic Martian dust devils and the fragile, dark surface of a comet that disintegrates as you try to land on it. Join the crew as they chart the inhospitable landscapes of our neighbouring planets and take a death defying fly-by of the Sun to accelerate them towards the outer giant planets and the forbidding, frozen worlds of Pluto and Charon. The story is told in the team s own words. Their mission may still be fiction, but their experiences are rooted in those of the real astronauts who have already flown to another world, and lived for months in orbiting space stations. Vivid images, inspired and informed by forty years of real robotic exploration of the planets, ensure that Space Odyssey is the most accurate portrayal possible of such a voyage until the day it becomes a reality.